2013
DOI: 10.1097/wnf.0b013e318279bcfa
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacology of Ponezumab (PF-04360365) After a Single 10-Minute Intravenous Infusion in Subjects With Mild to Moderate Alzheimer Disease

Abstract: Administration of ponezumab as a 10-minute infusion was safe and well tolerated and produced effects on plasma Aβ species comparable with a 2-hour infusion. Shorter infusions may provide more flexibility, comfort, and convenience for patients and caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 11 publications
(9 reference statements)
0
18
0
1
Order By: Relevance
“…Immunotherapeutic agents like bapineuzumab, solanezumab, gantenerumab, ponezumab and crenezumab have a high affinity to antigenic determinant epitopes of beta-amyloid 6 . They are then recognized by the B and T cells and cleared from the brain (Burstein et al 2013). A vaccine CAD106 undergoing phase 1 trial may be able to reduce beta-amyloid accumulation by binding to the amyloid aggregates and blocking cellular toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapeutic agents like bapineuzumab, solanezumab, gantenerumab, ponezumab and crenezumab have a high affinity to antigenic determinant epitopes of beta-amyloid 6 . They are then recognized by the B and T cells and cleared from the brain (Burstein et al 2013). A vaccine CAD106 undergoing phase 1 trial may be able to reduce beta-amyloid accumulation by binding to the amyloid aggregates and blocking cellular toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A short single intravenous infusion of ponezumab results in a very marked increase in plasma levels of both Ab42 and Ab40 (Burstein et al, 2013). This was verified in a phase I randomized, double-blind, placebo-controlled clinical trial in mild-to-moderate AD patients, which also showed that ponezumab, to a much lesser extent, increased the CSF Ab level (Landen et al, 2013).…”
Section: Passive Immunotherapymentioning
confidence: 71%
“…Ponezumab (PF-04360365) is a humanized monoclonal anti-Ab antibody with an epitope on the C terminus (AbX-40) of the Ab protein (La Porte et al, 2012;Burstein et al, 2013). Ponezumab binds only to soluble Ab, but not to fibrillar Ab or plaques, probably as the C terminus is not as exposed as the N terminus in Ab fibrils and plaques (Landen et al, 2013).…”
Section: Passive Immunotherapy With Anti-ab Antibodiesmentioning
confidence: 99%
“…Following these encouraging studies in mice, a phase I clinical trials was initiated. Reportedly, Ponezumab increased plasma and CSF Aβ 40 levels in a dose dependent fashion with minimal adverse effects (Burstein et al 2013; Landen et al 2013). Similarly, a phase II trial demonstrated increased plasma Aβ 40 levels with good tolerance.…”
Section: Passive Immunization Targeting Aβmentioning
confidence: 98%